The Urgency Of Restorative Justice In Imposing Criminal Sanction Under Law Number 1 Of 2023 Concerning The Criminal Code And Law Number 8 Of 1981 Concerning Criminal Procedure Law Viewed From The Judge's Perspective - Muhammad Cakranegara; Milda Istiqomah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Judges have the authority to receive, examine, and decide on criminal cases. With the promulgation of Law Number 1 of 2023 concerning the Criminal Code, Indonesia has new criminal law regulations, resulting in differences in punishment compared to the old Criminal Code. However, the theory of Restorative Justice, as outlined in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, is not included in Law Number 1 of 2023 concerning the Criminal Code. This omission leaves arrangements regarding Restorative Justice for adult legal subjects in Indonesia solely based on internal regulations from the Police, Prosecutor's Office, and Supreme Court. The problem arises when a case involves a Defendant who has compensated the victim for losses exceeding those suffered. This research concludes that judges have not been able to make decisions based on the theory of Restorative Justice because Law Number 1 of 2023 concerning the Criminal Code does not implement the principles of Restorative Justice based on the theories of Howard Zehr and Ali Gohar. Consequently, the Diversion Concept, as contained in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, should be applied to adult perpetrators if the criminal system in Indonesia aims to promote recovery for both criminals and their victims.